Preparation of MSZ Hydrogel and Its Treatment of Colitis - Wu, Yanhong; Li, Shangyong; Jin, Mengfei; Li, Dandan; Zhou, Zihan; Hou, Haiqing; Han, Yantao (Frontiers in Pharmacology, 2021)
In order to control the release of mesalazine (MSZ) in the gastrointestinal tract, so as to achieve better pharmacological effects in the colon, in this paper, MSZ was added to hydroxypropyl-β-cyclodextrin (HP-β-CD) to form water-soluble HP-β-CD/MSZ inclusion complex. Then the inclusion compound was loaded into the structure of the bilayer polyelectrolyte complex microsphere formed by alginate (Alg), chitosan (Cs) and kappa carrageenan (κ-Car) as the hydrogel carrier, and the hydrogel beads with colon specific release MSZ after oral administration were formed. The formed hydrogel beads have different swelling capabilities in different pH media and have the greatest swelling degree under pH 7.4. The encapsulation efficiency and drug loading of hydrogel beads can reach 83.23% and 18.31% respectively, and the size of hydrogel beads can be reduced to less than 1mm after drying, so that the size of oral administration can be reached. In vivo experiments also showed that the formed hydrogel had a better therapeutic effect on colitis than free drugs, and the microspheres were biodegradable, so the double-layer pH-sensitive microspheres could be effectively used in colon targeting drug delivery.